Geometric diffusion model for molecular generation - Mou, Bingyan (Nanyang Technological University, 2024)
Significant progress has been made in the field of deep generative models, with notable examples such as ChatGPT and image-generation tools like Midjourney, Stable Diffusion, and DALL·E showcasing remarkable performance. One of the key mathematical models behind these advancements is denoising diffusion models (DDMs, Ho et al., 2020; Song et al., 2021), which belong to a class of generative models aiming to reconstruct clean data from noisy observations. DDMs have demonstrated significant effectiveness in diverse applications, including image restoration, image inpainting, and generative modelling.